PENGARUH PENGGUNAAN MEDIA INTERAKTIF ASSEMBLR EDU TERHADAP HASIL BELAJAR IPA MATERI TATA SURYA KELAS VI SDN 104203 BANDAR KHALIPAH - Jelita Damai Yanti Haloho (STKIP Subang, 2026)
Science lessons on the solar system in elementary schools are often difficult for students to grasp because the subject matter is abstract and cannot be directly demonstrated in the classroom. Conventional media—such as printed images and lectures—are considered inadequate for providing a concrete learning experience for sixth-grade students, who are at the concrete operational stage of cognitive development. This study aimed to determine the effect of using the augmented reality-based platform Assemblr Edu on the cognitive learning outcomes regarding the solar system among sixth-grade students at SDN 104203 Bandar Khalipah. A quantitative approach was employed using a quasi-experimental design (specifically, a non-equivalent control group design) involving 47 students divided into an experimental group (n=24) using Assemblr Edu and a control group (n=23) using conventional media. Data were collected via multiple-choice tests and analyzed using the Shapiro-Wilk normality test, Levene’s homogeneity test, the independent samples t-test, and N-Gain calculations. The analysis revealed that the experimental group's average post-test score (78.83) was higher than that of the control group (51.58), with a significant t-test result (p < 0.05); the N-Gain score for the experimental group fell into the medium-to-high category (0.54), whereas the control group fell into the medium category (0.28). These findings conclude that the use of Assemblr Edu significantly improves students' cognitive learning outcomes regarding the solar system, thereby supporting its recommendation as an alternative learning medium for science education in elementary schools.